Mediation effect of training motivation on the relationships between trainee, training, organizational characteristic support, and overall training effectiveness - Abdul Aziz, Siti Fardaniah (2013)
Human resource development (HRD) field of study has emphasized the importance of training effectiveness; in which, training motivation is highlighted as an influential factor to determine training effectiveness. However, the existence of various types of training motivation makes it difficult to determine whether training motivation can play role as predictor and mediator. Therefore, the objective of the present research was to determine the prediction and mediation effect of comprehensive training motivation (CTM) on the relationships between trainee- (TCS), training program- (TPCS), and organizational- (OCS) characteristic support and overall training effectiveness (OTE) among academic staff in a public university in Malaysia. A research framework was developed by adapting and integrating motivational theory, training motivation model, training effectiveness model and previous researches to achieve the research objective. The research framework explains that CTM partially mediates the relationships between independent variables and OTE. In addition, the research used quantitative, survey, and prediction study. Respondents involved were 281 academic staff attended 17 general training programs provided by Centre for Academic Advancement in Universiti Kebangsaan Malaysia between April and July 2011. The instrument used in this research was checked for face validity, content validity, and constructs validity, as well as reliability, and confirmatory factor analysis. Data were analysed using structural equation modelling through SPSS and AMOS software; wherein, an exploratory data analysis was done to make sure the compliance of multivariate analysis assumption. Findings found some variations in the respondents’ background; in which, majority of respondents from various faculty/department have attended training as an option. Findings also found that the measurement and structural model to test for the research framework had sufficient goodness of fit; in which, the full was better than the partial mediation model. Majority of respondents perceived high level of OTE,CTM, OCS, TCS, and TPCS. In addition, OTE had a significant and positive relationship with independent variables. Further, it was found that CTM significantly mediated the relationship between TPCS and OTE with full mediation effect. However, CTM did not significantly mediate the relationship between TCS and OTE, and that between OCS and OTE. Additionally, CTM had a large effect on OTE (β = 0.645, p = .0001) and can explain 41% variance in OTE. Findings are consistent with some of previous research. Findings of this research contributes to the HRD field of study by adding new findings to the body of knowledge and verifying similar findings as demonstrated in Mprevious researches. This research is useful to inspire organization, future researcher,and the society to predict OTE by determining the level of CTM as an alternative of conducting rigorous training evaluation since the latter was expensive, complex, and time-consuming. Additionally, this research also offers a new perspective to improve training effectiveness by selecting the right TCS and TPCS, and providing the right OCS to stimulate training motivation that can be useful for future intervention. The research conclusion, implications, suggestions, and recommendations for future research are also discussed.